Efeitos da espessura de gordura, conformação, peso de carcaça e idade sobre a qualidade da carcaça e da carne de vacas de descarte - Donicht, Patrícia Alessandra Meneguzzi Metz (2011)
The objective was to analyse the effect of subcutaneous fat thickness (SFT), conformation (CONF), cold carcass weight (CCW) and age on carcass and meat quality of 152 Nellore cull cows and 240 Charolais cull cows. The data were submitted to a regression analysis by PROC REG and PROC STEPWISE procedures. Cold carcass yield was influenced by SFT (Y = 47.36274 + .45159x) and CCW (Y = 42.84735 + .02857x) in Nellore cull cows. It was observed, for Nellore cull cows, interaction equations for pistol cut percentage (Y = 48.3228 + .35761CONF - .00739 CCW), forequarter weight (Y = 68.64009 + .51448SFT + .06195CCW) and side cut weight (Y = 22.53615 + .33861SFT + .02735CCW). Nellore cull cows presented positively relation between Longissimus dorsi area and CCW, however it presented negativly relation with SFT (Y = 50.6691 - .47432SFT + .05012CCW). The accretion of 1 kg in CCW or 1 point in conformation of the carcass of Nellore cows resulted in an increase of .12 and 1.7 kg, respectively, in muscle weight. SFT and age influenced positively fat tissue and negatively muscle participation in carcass of Nellore cows. Muscle:bone relation increased with CCW and decreased with age advance in Nellore cows. For Nellore cull cows, the SFT had a quadratic relation with tenderness and shear force, presenting greater tenderness (5.3 points) when SFT had 7.8 mm and lower shear force (6.6 kgf/cm2) when SFT reached 5.6 mm. Each point increased in conformation of Charolais carcasses added 12 kg in slaughter weight, as well as 1 kg added to CCW represented adition slaughter weight of .4 kg. Pistol cut of Charolais cows, when expressed in kg, had positively relation to CCW, however had negatively relation to CONF. Each millimeter or kg added to SFT or CCW, in Charolais cows, resulted in a reduction of .4 and .04 cm2 in Longissimus dorsi area. Carcasses muscle and fat quantities of Charolais cows was positively influenced by SFT and CCW. However, age and conformation influenced negatively muscle and fat quantities, respectively, in Charolais cows carcasses. The addition of 1 kg of CCW increased in .003 points Charolais meat tenderness, while shear force presented a quadratic relation to SFT, being animals with 5.3 mm the ones with higher value for this characteristic (5.6 kgf/cm2).